2015
DOI: 10.1111/imm.12504
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dendritic cells to the autoimmune pathology of systemic lupus erythematosus

Abstract: SummarySystemic lupus erythematosus (SLE) is a heterogeneous disease in which excessive inflammation, autoantibodies and complement activation lead to multisystem tissue damage. The contribution of the individual genetic composition has been extensively studied, and several susceptibility genes related to immune pathways that participate in SLE pathogenesis have been identified. It has been proposed that SLE takes place when susceptibility factors interact with environmental stimuli leading to a deregulated im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 174 publications
(363 reference statements)
0
20
0
Order By: Relevance
“…Various organ system damage will be caused by SLE, as a consequence of the formation and deposition of autoantibodies and immune complexes. 10 The prevalence of mucosal involvement is present in approximately 9-45% of cases and accompanied by a systemic form of the disease. According to the literature, oral lesions occur more frequently in women with a female to male ratio that is 2.7 times greater.…”
Section: Introductionmentioning
confidence: 99%
“…Various organ system damage will be caused by SLE, as a consequence of the formation and deposition of autoantibodies and immune complexes. 10 The prevalence of mucosal involvement is present in approximately 9-45% of cases and accompanied by a systemic form of the disease. According to the literature, oral lesions occur more frequently in women with a female to male ratio that is 2.7 times greater.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disease which is characterized by multiple autoantibody production, formation of immune complexes that result in multiple tissue or organ damages 1 3 . It has been revealed that dysregulation of the immune system, including abnormal T-cell, B-cell, and dendritic cells (DCs) responses, participates in the pathogenesis of SLE 4 – 6 . However, to date, the exact pathogenic mechanism of SLE is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The impaired clearance of apoptotic cells observed in SLE and the opsonization of cellular apoptotic debris by autoantibodies enhances its uptake by pDC. Moreover, these apoptotic particles are able to induce the synthesis of IFN- α , which in turn favors the maturation of mDC and triggers isotype switching and autoantibody production by autoreactive B cells [ 24 26 ]. However, the role of ILT4 in the pathophysiology of this autoimmune disease has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%